PENGARUH MODEL PEMBELAJARAN BLENDED LEARNING TERHADAP HASIL BELAJAR PADA MATA PELJARAN PENDIDIKAN AGAMA ISLAM MATERI MENERAPKAN AL-KULLIYATUL AL-KHAMSAH DALAM KEHIDUPAN SEHARI-HARI KELAS X SMAN 2 PONTIANAK TAHUN AJARAN 2025/2026 - Rabi’ah, Putri; Eli; Elvri, Rini (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effect of the blended learning model on learning outcomes in the Islamic Religious Education subject—specifically regarding the topic of applying al-Kulliyatul al-Khamsah (the five fundamental objectives of Sharia) in daily life—among Grade X students at SMAN 2 Pontianak during the 2025/2026 academic year. The research questions addressed are: (1) What were the learning outcomes of Grade X students at SMAN 2 Pontianak in Islamic Religious Education (on the topic of applying *al-Kulliyatul al-Khamsah in daily life) prior to the use of blended learning? (2) What were the learning outcomes of Grade X students at SMAN 2 Pontianak in Islamic Religious Education (on the topic of applying al-Kulliyatul al-Khamsah in daily life) after using blended learning? (3) Is there an effect of using the blended learning model on learning outcomes in Islamic Religious Education (on the topic of applying al-Kulliyatulal-Khamsah in daily life) for Grade X students at SMAN 2 Pontianak? This study employs a quantitative experimental research method. The population consists of all Grade X students at SMAN 2 Pontianak, with Class X M9 designated as the experimental group and Class X M10 as the control group. Data collection was conducted via tests categorized into two types: a pre-test (administered before the treatment) and a post-test (administered after the treatment). Data analysis techniques included normality testing and hypothesis testing using the Wilcoxon test. The results indicate an improvement in student learning outcomes following the learning process, as evidenced by the Wilcoxon signed-rank test showing a significance value of 0.000 (p < 0.05), thereby confirming a significant difference between pre-test and post-test scores in the control class.